2015
DOI: 10.1245/s10434-015-5021-2
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Lymph Node–Positive Cases Based on Perirectal and Lateral Pelvic Lymph Nodes Using Magnetic Resonance Imaging: Study of the Japanese Society for Cancer of the Colon and Rectum

Abstract: Identification of LN-positive cases on the basis of PRLN and LPLN sizes was superior at a short-axis 5 mm cutoff. Size-based diagnosis of LN metastasis is simple and useful, but further investigation is needed to clarify whether it is superior to diagnosis based on morphology, such as shape, border, and signal intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 19 publications
3
44
0
Order By: Relevance
“…11). On the other hand, large lymph nodes such as ≥ 8 mm in short-axis diameter (56), ≥ 10 mm in short-axis diameter (57) or ≥ 10 mm in maximal diameter (54) were reported to be highly specific for nodal metastasis, albeit not sensitive. The Canadian guide for reporting of rectal cancer MRI (56) provides specific instructions regarding lymph node size that should be reported to be suspicious of metastasis, i.e., ≥ 8 mm and ≥ 10 mm in short-axis diameter for mesorectal and extramesorectal nodes, respectively.…”
Section: Elaboration On the Reporting Items Formats And Their Clinimentioning
confidence: 99%
“…11). On the other hand, large lymph nodes such as ≥ 8 mm in short-axis diameter (56), ≥ 10 mm in short-axis diameter (57) or ≥ 10 mm in maximal diameter (54) were reported to be highly specific for nodal metastasis, albeit not sensitive. The Canadian guide for reporting of rectal cancer MRI (56) provides specific instructions regarding lymph node size that should be reported to be suspicious of metastasis, i.e., ≥ 8 mm and ≥ 10 mm in short-axis diameter for mesorectal and extramesorectal nodes, respectively.…”
Section: Elaboration On the Reporting Items Formats And Their Clinimentioning
confidence: 99%
“…A recent meta-analysis reported that the sensitivity and specificity of MRI for diagnosis of pararectal and/or mesenteric lymph node metastasis of rectal cancer were 77% and 71%, respectively [6]. Regarding the pre-operative diagnosis of LPLN metastasis ability, five Japanese imaging studies using MRI and/or (MD) CT have been published (Table 4) [7][8][9][10][11]. The studies using MRI showed that the sensitivity, specificity, PPV, NPV, and accuracy were in the range of 43.8%-87%, 79.7%-98.5%, 43.6%-91%, 81%-97%, and 77.6%-88.1%, respectively, using a size criteria ranging from 4 to 10 mm at the short axis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, the sensitivity and specificity of MRI for the lymph node metastasis diagnosis were reported to be 77% and 71%, respectively [6], but this study only examined the perirectal (mesorectal) lymph nodes. Several studies from Japan reported the diagnostic value of MRI for the detection of LPLN metastasis in LRC without pre-operative therapy [7][8][9][10][11]. According to these studies, the sensitivity and specificity of MRI for the detection of LPLN metastasis were ranging between 43.8%-87% and 79.7%-98.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although accurate presurgical diagnosis of LPN metastasis is difficult, LPN size (as measured using imaging modalities) has frequently been used to predict the presence of metastasis. In a study of patients who did not undergo neoadjuvant CRT, the sensitivity and specificity of LPN size as a predictor of metastasis were 68.6-87% and 79.7-81.0%, respectively [9,10]. In a study of patients who did receive neoadjuvant CRT, the sensitivity and specificity of postneoadjuvant CRT LPN size were reported to be 67.7 and 84.8%, respectively [11].…”
Section: Introductionmentioning
confidence: 99%